Description of five new rheophilic Orthochromis species (Teleostei: Cichlidae) from the Upper Congo drainage in Zambia and the Democratic Republic of the Congo - Schedel, Frederic Dieter Benedikt; Vreven, Emmanuel J.w.m.n.; Manda, Bauchet Katemo; Abwe, Emmanuel; Manda, Bauchet Katemo; Schliewen, Ulrich Kurt (Zootaxa, 2018)
Five new rheophilic haplochromine cichlid species are described from the Upper Congo drainage of Zambia and the Democratic Republic of the Congo: Orthochromis mporokoso sp. nov. and O. katumbii sp. nov. from the Bangwelu-Mweru ecoregion, O. kimpala sp. nov. and O. gecki sp. nov. from the Upper Lualaba ecoregion, and O. indermauri sp. nov. from the Lufubu River of the Lake Tanganyika ecoregion. Orthochromis kimpala sp. nov, O. gecki sp. nov., and O. indermauri sp. nov. are distinguished from all currently valid species of the genus Orthochromis Greenwood 1954, except for O. torrenticola (Thys van den Audenaerde 1963), by the presence of eggspots or eggspot-like maculae on the anal fin (vs. no eggspots). The three species can be easily distinguished from O. torrenticola by having three anal spines (vs. four anal spines). Moreover, all five new species can be individually distinguished from all currently known rheophilic taxa placed in the genera Orthochromis, Schwetzochromis Poll 1948 and the rheophilic species of the genus Haplochromis Hilgendorf 1888 (e.g. H. bakongo Thys van den Audenaerde 1964, H. snoeksi Wamuini Lunkayilako & Vreven 2010, H. vanheusdeni Schedel et al. 2014) either based on meristic values, morphometric distances and colouration patterns, or on a combination of them.